Tellurium isotope fractionation during evaporation from silicate melts. (15th December 2022) - Renggli, Christian J.; Hellmann, Jan L.; Burkhardt, Christoph; Klemme, Stephan; Berndt, Jasper; Pangritz, Paul; Kleine, Thorsten
Abstract: As a moderately volatile, redox-sensitive chalcophile and siderophile element, Te and its isotopic composition can inform on a multitude of geochemical and cosmochemical processes. However, the interpretation of Te data from natural settings is often hindered by an insufficient understanding of the behavior of Te in high-temperature conditions. Here, we present the results of Te evaporation and isotopic fractionation in silicate melting experiments. The starting material was boron-bearing anorthite-diopside glass with 1 wt% TeO2 . The experiments were conducted over the temperature range of 868–1459 °C for 15 min each, and at oxygen fugacities (log f O2 ) relative to the fayalite-magnetite-quartz buffer (FMQ) of FMQ−6 to FMQ+1.5, and in air. Evaporation of Te decreases with decreasing f O2 . For high-temperature experiments performed at >1200 °C Te loss is accompanied by Te isotope fractionation towards heavier compositions in the residual glasses. By contrast, Te loss in experiments performed at temperatures <1200 °C typically resulted in lighter Te isotopic compositions in the residues relative to the starting material. In air, Te evaporates as TeO2, whereas at lower oxygen fugacities we predict the evaporation of Te2, using Gibbs free energy minimization calculations. In air, the experimentally determined kinetic isotopic fractionation factor for δ 128/126 Te at T > 1200 °C is αK  = 0.99993. At reducing conditions, Te likely substitutes as Te 2− for O 2– in the melt structure and becomes increasingly soluble at highly reducing conditions. Consequently, Te evaporation is not predicted for volcanic processes on reduced planetary bodies such as the Moon or Mercury.